INTEGRASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM MERDEKA: ANALISIS KONSEPTUAL BERBASIS LITERATUR - Ahmad Sammul Khairi; Akhmad Syahri; Musta'in (cendekia citra gemilang, 2026)
This study aims to analyze the integration of Islamic Religious Education (PAI) values within the Merdeka Curriculum through a literature-based approach. The research employs a qualitative method using library research combined with conceptual analysis of relevant scholarly sources. The data were collected from accredited journal articles, academic books, and policy documents published between 2020 and 2025, and analyzed using thematic analysis. The findings reveal that the integration of PAI values in the Merdeka Curriculum represents a transformation toward value-centered education, in which values are not merely taught but holistically internalized through meaningful learning experiences. Value integration occurs across various aspects of learning, including through the Pancasila Student Profile Strengthening Project (P5), and is supported by the strategic role of teachers as agents of value transformation. Furthermore, the integration also includes the reinforcement of religious moderation, emphasizing tolerance and inclusivity. However, the implementation still faces several challenges, including limited teacher pedagogical competence, the absence of systematic integration models, and the gap between curriculum design and classroom practice. Therefore, it is necessary to develop more applicable value-based learning models and enhance teachers’ competencies to effectively implement value integration.